Impact of pyrogenic carbon on tomato root architecture and metabolites (ABA and proline) under drought stress - Zhang, Yuan; Nisa, Rifat-un-; Saleem, Aansa Rukya; Nisa, Waqar-un-; Idris, Abubakr M.; Yu, Guo; Sohail, Muhammad Tayyab; Ullah, Habib (Frontiers in Plant Science, 2025)
IntroductionDrought stress severely threatens global agriculture by reducing crop productivity and compromising food security. Biochar derived from agricultural waste has emerged as a promising soil amendment to enhance plant resilience and mitigate drought impacts.MethodsThis study evaluated the effects of walnut shell biochar (WS biochar) at 3% and 5% (w/w) application rates on tomato (Solanum lycopersicum) growth under severe (45% field capacity) and moderate (75% field capacity) drought conditions. The biochar was characterized for physicochemical properties, and its impact on root architecture, biomass accumulation, and stress-related hormonal responses was assessed through greenhouse pot trials.ResultsWS biochar exhibited high conversion efficiency (58.8%), with favorable properties such as high fixed carbon content (98%) and porous macroporous structure enhancing soil water retention. The 5% biochar treatment increased plant height by 24%, improved leaf production, and mitigated a 92% biomass reduction under severe drought conditions. Root systems showed 30% longer primary roots and 25% higher lateral root density. Biochar treatments reduced oxidative stress markers, lowering proline accumulation by 18% and abscisic acid (ABA) levels by 22% under severe drought.DiscussionWalnut shell biochar effectively enhances tomato drought resilience by improving root development, biomass, and physiological stress responses. These improvements likely stem from enhanced soil water retention and modified hormonal signaling. The findings support WS biochar’s potential as a sustainable, climate-smart amendment to improve crop performance in water-limited environments. Further field studies are recommended to confirm long-term benefits on soil health and yield.